Analisis Kinerja Proyek Konstruksi Menggunakan Earned Value Management dan Microsoft Project - Amnifu, Lodia Semaya; Bria, Theresia Avila; Liem, Ferdinan Nikson; Kore, Desri Marfenita Hale; Banoet, Yusril Melkisedek (Syntax Corporation, 2025)
Delays and cost deviations remain common challenges in construction projects, particularly in government-funded projects where administrative and regulatory dynamics can influence implementation. This study aims to evaluate the time and cost performance of the construction of the Social Service Building of East Nusa Tenggara Province using the Earned Value Management (EVM) method integrated with Microsoft Project. The research employed a quantitative descriptive approach based on primary data from weekly progress reports and field observations, as well as secondary data such as the S-curve, Work Plan and Requirements (RKS), and unit price analyses. A total of 1,200 project activities were reconstructed in Microsoft Project to develop detailed scheduling, resource assignments, baseline estimation, and performance tracking. The results indicate that the project experienced significant delays at Week 34, with a Schedule Variance of –54.87% and a Schedule Performance Index of 0.45. However, the project remained under budget, reflected by a Cost Variance of 0.64% and a Cost Performance Index of 1.01. Projection analysis estimates that the project will be completed in Week 76, indicating substantial schedule slippage, although the cost at completion is predicted to remain below the original budget.